EFEKTIFITAS JENIS DESIKAN DAN KECEPATAN UDARA TERHADAP PENYERAPAN UAP AIR DI UDARA - Rosdanelli Hasibuan, Ivo Dian Sari Marbun (Universitas Sumatera Utara, 2018)
Dry air is widely used in many fields, but the excessive water vapor in the air will make some problem and should be minimized to get the required dry air. The purpose of this research to observe the effect of air velocity and various of desiccants on the absorption of water vapor in the air on the tray dryer. The process of absorption of water vapor in the air performed with variations of the normal air velocity, 1.2 m/s, 2.3 m/s, and 3.6 m/s or volumetric rate of 0.059 m3/s; 0.113 m3/s; 0.178 m3/s and the type of desiccant of silica gel, alumina, and zeolite. Adsorption of water vapor in the air by desiccant was done by weighing the mass of desiccant before and after being crossed by air every interval of 60 minutes for 3 hours. Humidity measurement are performed on the upstream and downstream of the tray dryer to obtain a decrease in air humidity. The highest moisture adsorption using silica gel was obtained at velocities of 2.3 m/s and 3.6 m/s with adsorption of 0.266 grams water vapor / grams adsorbent and 0.264 grams water vapor / grams adsorbent as well as humidity of final air of 0.0194 kg water vapor/ kg dry air and 0.0198 kg water vapor/ kg dry air . The highest adsorption of water vapor using alumina was obtained at velocities of 2.3 m/s and 3.6 m/s with adsorption of 0.147 grams water vapor / gram adsorbent and 0.140 grams water vapor / gram adsorbent and the final humidity of 0.0207 kg water vapor / kg dry air and 0.0194 kg water vapor / kg dry air and the highest water vapor adsorption using zeolite was obtained at 3.6 m/s with the adsorption capacity of 0.130 grams water vapor / grams adsorbent and the final humidity of 0.0193 kg water vapor / kg dry air. Silica gel was the best desiccant in the process of moisture adsorption in air compared to alumina and zeolite.